Stress-path on the Hydraulic Fracturing Test of the Clay Core of Rock Fill Dams in the Laboratory. (2015) - Djarwadi, Didiek; Suryolelono, Kabul B.; Suhendro, Bambang; Hardiyatmo, Hary C.
Abstract: Hydraulic fracturing on the rock fill dam is described as a phenomenon of cracks on the upstream face of clay core of rock fill dams due to the tension failure. This situation may arise if the total stress in the core is reduced by arching effect and increasing pore water pressure in the core during impounding. Hydraulic fracturing on the rock fill dams can be modelled in the laboratory. The reduction of the total overburden stress due to arching effect and hydraulic pressure from the water in the reservoir can be modeled in the laboratory by applying the initial stress states and water pressure to the specimens. The soil specimens were compacted in a hollow cylinder. The dimension of the soil specimen was 100 mm in diameter and 120 mm high, while the inner diameter of the borehole was 18 mm. The paper present an initial hydraulic fracturing test at 5 (five) different initial stress states in order to investigate the tension fracture mechanism. The stress paths during hydraulic fracturing tests indicated the tension fracture to the soil specimens occurs on the soil specimens which the initial stresses fall in the envelope of ½(σy - σx ) < c.